Law Enforcement Policy in the Case of Double L Pill Abuse by Adolescents: A Study of the Ponorogo District Court Decision - Febriana, Refi Nur Eka; Isnandar, Aries; Irawan, Ferry (Jurnal Ilmiah Global Education, 2026)
The misuse of Double L pills among adolescents poses a serious threat to public health, moral values, and the future of the younger generation, including in Ponorogo Regency. This research analyzes Court Decision No. 75/Pid.Sus/2025/PN Png using a normative juridical approach to examine the judges’ legal considerations in proving the elements of the criminal act, the application of Article 435 of Law No. 17 of 2023 on Health, and the imposition of sanctions on juvenile offenders from the perspectives of legal certainty, justice, and social utility. The study reveals that the panel of judges successfully proved all elements of the offense in a lawful and convincing manner, making the application of Article 435 appropriate and reflective of strong legal certainty. The defendant was sentenced to 2 years and 6 months imprisonment, with the defendant’s young age and cooperative attitude considered as mitigating factors. Nevertheless, the aspects of substantive justice and utility, particularly regarding the guidance and rehabilitation of juvenile offenders, remain less than optimal. The research concludes that stronger collaboration among law enforcement agencies, local government, educational institutions, and the community is required through intensive legal education, early prevention, and recovery-oriented rehabilitation programs. Such measures will ensure that law enforcement is not merely retributive but also preventive and educative for the younger generation.